Visit from Vice-Chancellor of UiTM to AAGBS - UiTM, Arshad Ayub Graduate Business School (Arshad Ayub Graduate Business School, 2020)
A visit from the Vice-Chancellor of Universiti Teknologi MARA to the Arshad Ayub Graduate Business School (AAGBS) was held with Profesor Emeritus Datuk Ir Dr Mohd Azraai Kassim, Vice-Chancellor of UiTM, as the special guest. The visit aimed to strengthen engagement between the university’s top management and the academic community at AAGBS.